Literature Review: Gangguan Mental Depresi Pada Wanita - Kurniasari Pratiwi; Dinik Rusinani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
ABSTRACT Depression is a form of mental health condition experienced by many people and often occurs along with anxiety. Depression can be mild and transient, or severe and prolonged. There are people who experience depression only once in their life; some have experienced it many times. Depression is one of the main causes of suicide (suicide). Based on the data as much as 40% of patients depressed people have suicidal ideation, and only about 15% are successful in doing so. WHO predicts that by 2020, depression will be one of the most common mental disorders and major depression will be the second leading cause of death after heart attacks. Depression is a mental disorder characterized by a prolonged feeling of sadness and loss of interest in activities that are usually done with pleasure. Signs of depression include a bad mood such as prolonged sadness, hopelessness, feelings of guilt and meaninglessness so that all mental processes (thinking, feeling and behaving) can affect motivation to engage in activities in daily life and interpersonal relationships. Another sign of depression is stopping your usual daily activities for at least two weeks. Keywords: Depression, women, literature review